Condition monitoring on vibration characteristics of rolling element bearings - Ting, Benson Sze Ling. (unimas, 1999)
The useful life of rolling element bearings can be significantly shorter than their design life due to factors in their operating environment. To prevent potentially unexpected bearing failure effective condition monitoring is required. Vibration is a study of oscillatory motions. The ultimate goals of this study are to determine the effect of vibration on the performance and safety of systems, and to control its effects. With the advent of high performance machines and environmental control, this study has become a part of engineering curricula. The vibration and dynamics analysis of mechanical systems is becoming increasingly complex today, and it will continue to do 80 in order to meet the challenges and demands of21t1l century technology.